(untitled) (Research, Society and Development, 2024)
Introduction: Tumors in the appendix are rare and often underdiagnosed until histopathological examination. Its clinical features resemble acute appendicitis, leading to most emergency diagnoses and urgent appendectomies. Appendiceal malignancies include epithelial and non-epithelial tumors, with mucinous carcinoids being the most common subtype. The objective of this study is to report the case of a patient with cecal appendix cancer. Case Report: A 26-year-old patient arrived at the hospital with typical symptoms of appendicitis. Tests revealed suspected acute appendicitis, leading to an emergency appendectomy. Histopathology revealed low-grade mucinous neoplasm in the appendix (LAMN), without invasion. The patient recovered well after surgery.Methodology: The study consists of a case report of a patient with suspected acute appendicitis whose postoperative histopathology revealed LAMN, without invasion. The report was written with the participant’s permission through an Informed Consent Form read and signed by the patient.Discussion: LAMN often resembles acute appendicitis. The anatomopathological analysis is crucial for the diagnosis and imaging exams help with evaluation and staging. MRI is useful for this purpose. Surgeons must be prepared to deal with benign or malignant changes. Conclusion: This case emphasizes the importance of correctly diagnosing and treating cecal appendix cancer, a rare condition that mimics acute appendicitis. Accurate clinical and histopathological evaluation and postoperative follow-up are required. It is recommended for future studies to investigate clinical variations, develop biomarkers and evaluate adjuvant therapies.